BOOK REVIEW: "Documenta Pragensia XXXIII: Město v převratech konfesionalizace v 15. až 18. Století" ["Documenta Pragensia XXXIII: The Town in the Upheaval of Confessionalization between the Fifteenth Century and Eighteenth Century"], Praha, Scriptorium, 2014, 758 p., ISBN: 978-80-86852-67-6 (Archiv hl. m. Prahy); ISBN: 978-80-88013-24-2 (Scriptorium) - OANCEA, Sever (Studia Universitatis Babeș-Bolyai Historia, 2018)
The confessionalization represents one of the mostly researched topics of Early Modern History during the last four decades. It is an offspring of the German historiography and it engendered acute discussions on its use and relevence for the historical research, it became a battle field between different universities and chairs from Germany (Heinz Schilling/Wolfgang Reinhard) and Switzerland (Peter Hersche), it succeeded to cross the Germanic academic border, sometimes even without a minimal analytical filter. Nonetheless all these discussions and approaches contributed to a better understanding of certain historical processes. After the fall of Communism in Eastern Europe the confessionalization paradigm conquered the historical discourse in Poland, Czech Republic, Slovakia, Hungary and to a certain extent also Romania. Although the town enjoyed an important role within the confessionalization research in Western Europe, less has been said in East-Central Europe and therefore the present book is more than welcome: the thirty five authors focus on a large areal, the Czech Lands, Germany, Austria, Poland, Slovakia and Hungary, they cover a variety of topics from different perspectives.